Likert Scale vs Semantic scale: Comparing the use of Mendeley application for the journal editors - Fajaruddin, Syarief; Setiawati, Farida Agus; Setiawan, Ari; Astuti, Nuryani Dwi; Wiradika, I Nyoman Indhi; Nadia, Mia Ayu; Andi, Tri (Patria Educational Journal (PEJ), 2025)
The study aims to identify the excellence in the use of two types of scale by comparing the Likert Scale and the Semantic Differential Scale. In addition, the study aims to identify the constructs of the Mendeley application as well as the indicators that it has shaped. The study itself is developmental research. The instruments for the Likert Scale and the Semantic Scale have been developed by referring to the same guidelines. Then, the respondents in the study are 59 journal administrators throughout Indonesia. After the data have been gathered, the data are analysed by using the exploratory factor analysis and the confirmatory factor analysis. The results of the study show that four factors that have been formed in the construction for the Mendeley application using the two scales. Based on the measurement results, it is found that Semantic Differential Scale is more excellent in terms of validity and reliability.